PROFIL DARAH DAN STATUS GIZI PETUGAS OPERATOR SPBU YANG TERPAPAR GAS BUANG (Pb) KENDARAAN BERMOTOR DI KOTA SEMARANG TIMUR - Mifbakhuddin -; Ulfa Nurulita (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Background, Lead (Pb) constitutes as main pollutant in the air of the cities except sulphur dioxide (SO2), suspended particulate matter, nitrogen oxide (NOX ), and carbon monoxide (CO). The impacts of lead (Pb) exposure to health are kidney disorder, hypertension, anemia, central nerve disorder, behaviourial changes, fertility disorder, miscarriage, child’s IQ decrease, and the obstruction in the formation of hemoglobin. Objective, the description blood profile and nutrition status gas station workers   exposure in  the  easternt Semarang City. Method, the research is analytic observational uses cross sectional design with the number of samples 39 people. variable is  blood profile and the nutrition status. Results, the blood profile catch with the level of haemoglobin, leucosyt, hematocrit, erytrocite, MCV, MCH, MCHC, still in normal limits,  nutritional status most gas station workers the level normal. Conclusion, the no significant correlation  blood profile (haemoglobin, leucosyt, hematocrit, erytrocite, MCV, MCHC with nutrition status, the significant correlation blood profile (MCH) with nutrition status.  Suggestion, it is recommended that the gas station worker swear the self protective device (masker) while working in the gas station order to reduce the exposure of lead (Pb) from the motor vehicle exhaust and perform regular medical checkup with certain interval (at least once a year).Key words  :, blood profile, nutrition status,  gas attendants.